Philippine medical thesaurus on psychiatry and psychology behavior and behavior mechanisms in Bicol - Risbud, Vidya S. (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study sought to translate terms from the Medical Subject Headings (MeSH) Facet F01 - Behavior and Behavior Mechanisms and to create Philippine Medical Thesaurus on Psychiatry and Psychology: Behavior and Behavior Mechanism in Bicol. The top-down approach or method, a basis of the framework of the domain analysis, was utilized to create thesaurus in Bicol. It uses existing implementations, the Medical Subject Headings (MeSH) in particular and ranked translation tools and supplements.